Combined treatment with paraffin, manual therapy, pegboard and splinting in a patient with post-traumatic stiff hand. Issue 1 (December 2016) - Santacreu, Eva; Cabezas, Núria; Graupera, Asunción
Abstract Background The stiff hand is a still common, severe complication of hand injuries. Case presentation We report here the case of a 56 year-old woman, professional goldsmith, who suffered a distal radius fracture of her right hand. The patient was treated with surgery followed by four weeks of immobilization, and developed a stiff hand. Physical examination showed mild inflammatory signs, pain and a major limitation in the extension and supination of the wrist, and in the mobility of the II, III, IV and V metacarpophalangeal (-5° and 32° of average passive extension and flexion, respectively) and interphalangeal (-35° and 73° of average passive extension and flexion, respectively) joints. There was a lack of slip of the flexor tendons. The diagnosis of complex regional pain syndrome was considered although it could not be definitely established. After five months of adverse evolution the patient was referred to our center where a combined intervention with paraffin, manual therapy, prolonged active and passive stretch on a pegboard, and splinting was applied. After initiation of this therapy, a marked change in the evolution of the pain, the mobility and functionality of the hand was observed. At the end of the rehabilitation program the patient was able to fully resume her job. Conclusion The present case illustrates the need of intensive treatment for post-traumatic hand stiffness, and describes, as an original contribution, a combined intervention therapy including paraffin, manual therapy, pegboard and splinting.